PERBANDINGAN KONSUMSI BAHAN BAKAR ANTARA BUS DAN TRAVEL MINIBUS RUTE SEMARANG – SOLO SAMPAI TAHUN 2040 MENGGUNAKAN SOFTWARE LEAP - Noviyanto Rahmat Zulem; MSK. Tony Suryo Utomo (JURNAL TEKNIK MESIN, 2015)
The increasing number of vehicles with high fuel consumption and weak emission control policies negatively impact the environment. This research designed to projecting comparison of enery consumption of fuel and exaust emissions on bus and travel minibus route Semarang – Solo on 2013- 2040 using LEAP software with two scenarios, as for these scenarios is business as usual (BAU).Test results using LEAP shows the amount of fuel required bus in 2040 based on the BAU scenario amounted to 1.559.800 Gigajoules or to 43.448.467 liters of diesel fuel and 609.700 Gigajoules or 16.983.286 liters of diesel fuel based on the 2040 AFE scenario or fuel savings up to 39 % . The amount of fuel required for travel minibus based on the BAU scenario in 2040 was 1.333.000 Gigajoules or 37.130.919 liters of diesel fuel and 1.308.300 Gigajoules or 37.130.919 liters of diesel fuel based on the 2040 AFE scenario or savings up to 5  %.Carbon Dioxide Non Biogenic emissions produced by buses and travel minibus in 2040 for the AFE scenario decreased by 45 % compare to BAU scenario, but the value of  NOx and CO in scenario AFE decrease 20 % compare to BAU scenario.